DAMPAK ANCAMAN RESESI EKONOMI DUNIA TERHADAP INDUSTRI KELAPA SAWIT - Sutejo Parangin Angin; Aiyub Yahya; Ayu Angelina Pasaribu (Politeknik Negeri Lhokseumawe, 2023)
The increasing global demand for vegetable oils over the last few decades has led to an increase in income in every country in the world in the palm oil industry. The palm oil industry has contributed to economic growth as well as triggering increased incomes, creating jobs, and reducing poverty among agricultural and non-agricultural households. The World Bank also announced a complaint with the theme Commodity Markets Outlook: The Impact of the War in Ukraine on Commodity Markets. The consequences of the Russo-Ukraine War in the 2022 period resulted in an increase in world commodity prices due to the response to the Russian-Ukrainian war. With both complaints reported, the whole world must take steps to mitigate the threat of inflation and economic recession in the next three years (2022-2023). This research uses a literature review approach. In this literature review, it is found that the world economy is expected to experience a recession accompanied by inflation (stagflation). Internationally, slowing economic growth could weaken the purchasing power of the global community. In Europe, India, China, sub-Saharan Africa and North Africa, which are the main market areas for palm oil, economic growth has slowed and inflation has been relatively high. This situation has caused the purchasing power of palm oil importing countries to decline due to the economic recession and production costs to increase due to high global inflation. Keywords: World economic recession, Inflation, Palm Oil Industry.